Qualitative analysis of fourth-order hyperbolic equations - Andreieva, Yuliia; Buryachenko, Kateryna (Frontiers in Applied Mathematics and Statistics, 2024)
We investigate the qualitative properties of weak solutions to the boundary value problems for fourth-order linear hyperbolic equations with constant coefficients in a plane bounded domain convex with respect to characteristics. Our main scope is to prove some analogue of the maximum principle, solvability, uniqueness and regularity results for weak solutions of initial and boundary value problems in the space L^2.